2008
DOI: 10.1073/pnas.0712259105
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs and the advent of vertebrate morphological complexity

Abstract: The causal basis of vertebrate complexity has been sought in genome duplication events (GDEs) that occurred during the emergence of vertebrates, but evidence beyond coincidence is wanting. MicroRNAs (miRNAs) have recently been identified as a viable causal factor in increasing organismal complexity through the action of these Ϸ22-nt noncoding RNAs in regulating gene expression. Because miRNAs are continuously being added to animalian genomes, and, once integrated into a gene regulatory network, are strongly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
343
1
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(374 citation statements)
references
References 43 publications
20
343
1
10
Order By: Relevance
“…Rare genomic changes have also provided some evidence in its favor: the domain structure of cadherins (Oda et al, 2002), a unique amino-acid insertion in fibrillar collagen (Wada et al, 2006), and the distribution of micro RNAs (miRNAs) (Heimberg et al, 2008). Finally, the Branchiostoma floridae genome helps confirming the sistergroup relationship between tunicates and vertebrates in offering additional evidence from analyses of intron dynamics (Putnam et al, 2008).…”
Section: Corroborative Evidence For Olfactores Monophylymentioning
confidence: 99%
See 1 more Smart Citation
“…Rare genomic changes have also provided some evidence in its favor: the domain structure of cadherins (Oda et al, 2002), a unique amino-acid insertion in fibrillar collagen (Wada et al, 2006), and the distribution of micro RNAs (miRNAs) (Heimberg et al, 2008). Finally, the Branchiostoma floridae genome helps confirming the sistergroup relationship between tunicates and vertebrates in offering additional evidence from analyses of intron dynamics (Putnam et al, 2008).…”
Section: Corroborative Evidence For Olfactores Monophylymentioning
confidence: 99%
“…The comparison of miRNA repertoires in metazoans has also recently unearthed some potential signatures for the sister-group relationship of tunicates and vertebrates (Heimberg et al, 2008). miRNAs are small noncoding RNAs involved in regulation of gene expression in eukaryotes and play an important role in the development of metazoans.…”
Section: Corroborative Evidence For Olfactores Monophylymentioning
confidence: 99%
“…1B and Table 1), and found that major expansions of the new human miRNA family emergence also coincides with the advent of vertebrates, mammals and primates. Heimberg et al [8] found that a greatly expanded set of miRNAs have occurred in vertebrates as compared with bilaterian invertebrates and also identified 41 miRNA families evolved at the base of vertebrate. However, in our study, we revealed 72 miRNA families emerged from the vertebrate lineages, and further found that the number of the new human miRNA family reached a peak in the mammalian lineage.…”
Section: Evolutionary Distribution Of Human Mirnasmentioning
confidence: 99%
“…The phylogenetic distribution and evolution of animal and plant miRNAs have been studied in recent reports [2][3][4][5][6][7][8][9][10][11][12]. In animals, the expansion of miRNAs is an ongoing process [5].…”
Section: Introductionmentioning
confidence: 99%
“…Other ways that new miRNAs can arise include the modification or duplication of pre-existing miRNAs [108]. A rapid increase in the diversity of miRNAs in existing genomes is often correlated to a burst of new morphological diversity, and thus miRNA may be crucial to the development of complex morphologies because of its regulatory activity [71,110,134].…”
Section: Evolution Of Mirnamentioning
confidence: 99%